Effects of Acupuncture in the Treatment of Dogs with Neurological Sequels of Distemper Virus - Santos, Bianca P. C. R. [UNESP]; Joaquim, Jean G. F.; Cassu, Renata Navarro; Pantoja, José C. F. [UNESP]; Luna, Stelio Pacca Loureiro [UNESP] (Medical Association of Pharmacopuncture Institute, 2022)
Background: Acupuncture (AP) has been empirically used to relieve post-canine distemper virus (CDV) infection neurological signs in veterinary clinics. Objectives: This clinical study aimed to investigate the effects of AP combined with electroacupuncture (EA) on neurological function in dogs infected by CDV. Methods: Twenty-four CDV-infected dogs with neurological sequelae were recruited to receive weekly AP/EA sections for 24 weeks. Neurological improvements were assessed before each AP/EA session using a modified scoring system. Data were analyzed using the McNemar test, Friedman test, Fisher's exact test, and Kaplan-Meier curves (p < 0.05). Results: Neurological scores improved from seven to 24 weeks after AP/EA treatment compared with pretreatment scores (p < 0.001). Significant improvements were recorded over time for functional limb recovery, cranial nerve deficits, mental status (p = 0.025 – 0.014), and urinary function (p < 0.001). Myoclonus was improved and entirely reversed in 75% and 25% of the dogs, respectively. At the end of treatment, the proportion of dogs with normal proprioception, posture, hopping (p < 0.001), and superficial pain sensation responses (p = 0.004) was greater than pretreatment values. Conclusion: AP/EA therapy promoted significant neurological recovery in CDV-infected dogs and may be considered within the chronic phase of the disease to improve motor and sensory rehabilitation. However, these results are preliminary and must be confirmed by further investigations.
Keywords: Acupuncture; Canine distemper; Electroacupuncture; Neurological disorders; Rehabilitation